2020
DOI: 10.1177/1524500420918842
|View full text |Cite
|
Sign up to set email alerts
|

Normative Influence on Household Waste Separation: The Moderating Effect of Policy Implementation and Sociodemographic Variables

Abstract: Background: With the increasing production of domestic waste in South African urban areas, household waste separation has become a crucial recycling activity for better management of domestic waste and a decrease in environmental pollution. Focus of the article: This empirical study investigates how normative influences can shape the intention to separate household waste and how these influences are moderated by sociodemographic attributes and upstream social marketing interventions (recycling policy implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The social community's influence functions as a normative force that could impel people to act according to socially accepted codes of conduct (Kallgren et al, 2000). In the consumer literature, social influence plays a key role in shaping people's conative behaviors, leading to a higher level of purchase propensity and behavior (Issock et al, 2020). Accordingly, we propose the following hypothesis:…”
Section: Social Influencementioning
confidence: 99%
“…The social community's influence functions as a normative force that could impel people to act according to socially accepted codes of conduct (Kallgren et al, 2000). In the consumer literature, social influence plays a key role in shaping people's conative behaviors, leading to a higher level of purchase propensity and behavior (Issock et al, 2020). Accordingly, we propose the following hypothesis:…”
Section: Social Influencementioning
confidence: 99%
“…Despite the global nature of environmental problems, very little research in the IGT of environmental concern has been done outside the Western, educated, industrialised, rich, democratic (WEIRD) contexts. Additionally, substantial studies have shown the importance of normative influences as a promoting and suppressing factor of environmental actions (Issock et al., 2020; Vesely & Klöckner, 2018), especially in non‐Western contexts (Ando et al., 2015; Greenspan et al., 2021). However, there is a dearth of studies that have taken into account the role of culturally relevant factors in the IGT of environmental concern in non‐WEIRD contexts.…”
Section: Environmental Issues In the Philippinesmentioning
confidence: 99%
“…Vesely and Klöckner (2018) explained that people are more likely to engage in pro‐environmental behaviours that they perceive as socially appropriate. For instance, evidence has shown that norms influenced household waste separation among people living in urban South Africa (Issock et al., 2020). Field experiments have shown that being informed about normative practises in water use significantly reduces water consumption (Schultz et al., 2016).…”
Section: Environmental Issues In the Philippinesmentioning
confidence: 99%
“…Traditional methods such as surveys and interviews were the most frequently mentioned, while for example ethnography, a method highlighted by Gordon et al (2016) as being underutilized in social marketing, was not one of the 1000 most frequently mentioned words across all papers at the WSMC19. This is reflected in the published research outputs from the conference, with the majority using one of these two methods (Cook et al, 2020; Issock et al, 2020; Mulally et al, 2020).…”
mentioning
confidence: 99%
“…The WMSC 19 unfortunately seemed to follow the trends of past editions, with the top five mentions going to western geographies (Figure 3). That said, it is worth noting that two out of seven papers included in the Social Marketing Quarterly virtual special issue resulting from WSMC19 are from less traditional geographies, namely from Jordan and South Africa (Issock et al, 2020; Khayame & Abdeljawad, 2020). Noteworthy is the inclusion of the Greek city of “Trikala” in the most frequently mentioned terms (Figure 3), a result of two papers around the “Trikala Quits Smoking” Program, an intervention designed to support a ban on smoking in enclosed public spaces (see Skerletopoulos & Makris, 2020).…”
mentioning
confidence: 99%